Depopulation, Deindustrialisation and Disasters Building Sustainable Communities in Japan - Shiraishi, Katsutaka; Matoba, Nobutaka; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
Depopulation, Deindustrialisation and Disasters are three of the biggest problems facing Japan today. This book discusses how sustainable communities are being created in Japan in an attempt to overcome the threat of the triple Ds . It provides an overview of how each of these three core issues endangers the sustainability of local communities especially, but also discusses how they might also provide an opportunity to replace outdated paradigms, rooted in expansion and competition, with a new way forward on a global scale. The authors explore how the Japanese government has followed the worldwide trend of implementing neo-liberal policies in response to globalisation and how these policies have resulted in a mass exodus into larger cities such as Tokyo, leaving local communities more vulnerable to socio-economic threats. The authors highlight non-metropolitan areas facing the 'triple D' threat and introduce several case studies on how these are working towards achieving a more sustainable future. Written by members of the LORC (Research Centre for the Local Public Human Resources and Policy Development, Ryukoku University) this collection will be invaluable to scholars across the social and political sciences and to those interested in how innovative policy making can positively influence sustainable development. Katsutaka Shiraishi is Professor at the Faculty of Policy Science, Ryukoku University, Japan and has acted as the LORC's Director between 2008 and 2011 and again since 2014. He is also the chair of the board of the Kyoto Alliance, a collaborative platform between universities, local governments, business organisations and non-profit organisations (NPOs) in Kyoto. Nobutaka Matoba is Professor at the Faculty of Policy Science, Ryukoku University, Japan and has acted as the LORC's Deputy Director since 2014. He obtained a PhD from the University of Birmingham in the United Kingdom.
PART I Japan as the epitome of the triple Ds in the world -- Chapter 1 Global Trends in Facing the Triple Ds: Dynamics, Challenges, and Opportunities; Thorsten Wiechmann -- Chapter 2 Japanese Democracy in the Era of the Triple Ds; Kazuaki Nagatomi -- Chapter 3 Decentralisation and the Triple Ds in Japanese Municipalities; Kimie Tsuchiyama -- Chapter 4 Japanese Governance and Meta-governance; Tatsuro Niikawa -- Chapter 5 Kyoto Alliance for Local Public Human Resource Development; Tomomi Kubo & Kazuyo Murata -- PART II Depopulation -- Chapter 6 A New, Sustainable Form for Farming Villages and the Role of Migrants from the City; Naoko Oishi -- Chapter 7 Prospects and Challenges of the Social Security System and in Realising "Regional Cohesive Societies"; Kanako Imasato -- Chapter 8 Sustainable Medical Care Systems in Areas with a Declining and Aging Population: A Consideration of the Northern Part of Kyoto Prefecture as a Case Study; Nao Toyoda & Hiroshi Yahagi -- Chapter 9 The Emerging Food Desert in Kyoto: A New Challenge for Planners for a Sustainable and Health Living in the Built Environment; Daisuke Abe -- PART III Deindustrialisation -- Chapter 10 Impact of Industrialisation on Cities in Japan: The Past and Future of Osaka; Mayuko Shimizu -- Chapter 11 Issues with Japan's Agricultural Subsidies, which are Resistant to New Situations: Focusing on the Case Study of Morimoto District, Kyotango City, in the Northern Area of Kyoto Prefecture; Hong Shi Jin -- Chapter 12 Energy Governance: Mainstreaming Energy Policy for Local Sustainability; Nobutaka Matoba -- PART IV Disasters -- Chapter 13 Formation and Development of "Disaster Resilience Theory" in Japan; Ryoga Ishihara -- Chapter 14 Tohoku Food Communication as a Case Study of the New Economy in Post Disaster-Affected Tohoku, Japan; Fumihiko Saito -- Chapter 15 The Development of Disaster Management Laws and Systems after the Great East Japan Earthquake, and Local Resilience; Naofumi Ota -- Chapter 16 Impacts of the Fukushima Nuclear Power Plant Accident on Nuclear Policies; Kenichi Oshima -- Chapter 17 Community Foundations and Social Investments in Japan; Masataka Fukao -- 18. Conclusion; Katsutaka Shiraishi.
Keywords: Human geography; Sociology, Urban; Human Geography; Urban Sociology